Larissa and Piasus in the Suda Lexicon - Paradiso, Annalisa (Histos, 2026)
A number of Suda entries (s.v. ἀθέμιστα (Α 714 Adler) and s.v. Πίασος (Π 1549 Adler), and possibly also s.v. ἔωσεν (Ε 1909 Adler) rather than s.v. ἕρμα (Ε 3022 Adler)) deal with the myth of Larissa and her father Piasus, who fell in love with her, raped her, and was murdered by her. The anonymous quotations these entries preserve have been attributed to either Nicolaus of Damascus or Aelian. A linguistic investigation confirms the authorship of the latter.